WIND ENERGY POTENTIAL ASSESSMENT OF UKRAINE - YEVGEN MAKAROVSKIY; VIKTORIIA ZINYCH (Revue Roumaine de Géographie)
The article presents a methodology for theoretical and technically achievable wind power potential assessment, developed in the framework of EnviroGRIDS Black Sea Catchment project. The methodology has considerable advantages: it contains a simple algorithm, minimum set of input data, at the same time it provides highly reliable results and allows adequately assess wind power potential of investigated area. Developed methodology was tested on wind power potential of Ukraine.